Implementasi Green Pesantren Sebagai Model Manajemen Pendidikan Islam Berbasis Lingkungan - Wulan Oktarina; Rahmani Uswatun Khasanah; Exsy Setiawan; M. Daffa Abhiyasa; Diyah Puspita Sari; Cindi Amanda Nabila Sari (CV. ITTC INDONESIA, 2026)
The escalating environmental crisis requires educational institutions, including Islamic boarding schools (pesantren), to play an active role in fostering ecological awareness grounded in Islamic values. However, in practice, the management of Islamic boarding school education tends to focus primarily on academic and religious aspects without systematically integrating environmental concerns. In fact, Islamic teachings emphasize the role of humans as khalifah (stewards) on earth who are responsible for preserving environmental sustainability. This study aims to formulate and describe the implementation of the green pesantren concept as an environmentally based model of Islamic educational management that integrates institutional aspects, curriculum, culture, and sustainable facilities management. This study employed a library research method with a descriptive qualitative approach by reviewing various books, scientific journals, and relevant studies on Islamic educational management, environmental education, and Islamic ecotheology. The findings indicate that the implementation of green pesantren can be realized through environmentally friendly institutional policies, the integration of environmental values into the curriculum, the establishment of an environmentally conscious pesantren culture through habituation and role modeling, and the management of facilities and infrastructure, including waste management, water conservation, and greening programs. Collectively, these efforts can enhance ecological awareness and shape students' character to become environmentally responsible individuals. Therefore, the green pesantren model can be regarded as a strategic solution for developing a holistic and sustainable model of Islamic educational management, as it balances the intellectual, spiritual, and socio-ecological dimensions of learners in responding to global challenges.